Content analysis of UPSEC fundamentals of physics - Donato, Alejandro P. 1942-; Montales, Penafort J., joint auth.; Tan, Elsa G., joint auth. ([Quezon City s.n.], 1974)
An attempt to make a content analysis of the UPSEC Fundamentals of Physics Textbook was presented in this study. The analysis involves the detailed description of the two profiles, namely: An Index of Student Involvement and Word Loading. A quantitative rating scheme has been followed in establishing student involvement. For the vocabulary load, unfamiliar technical and non-technical terms have been identified. Their rate of appearance, frequency of use and gaps between usage were also analyzed.
Thesis (M.A.T.Physics)--University of the Philippines.
Keywords: Philippines. University -- Science Education Center; Physics -- Text-books.